2010
DOI: 10.5194/asr-4-63-2010
|View full text |Cite
|
Sign up to set email alerts
|

On the role of the planetary boundary layer depth in the climate system

Abstract: Abstract.The planetary boundary layer (PBL) is a part of the Earth's atmosphere where turbulent fluxes dominate vertical mixing and constitute an important part of the energy balance. The PBL depth, h, is recognized as an important parameter, which controls some features of the Earth's climate and the atmospheric chemical composition. It is also known that h varies by two orders of magnitude on diurnal and seasonal time scales. This brief note highlights effects of this variability on the atmospheric near-surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…Among the many processes that have been considered responsible for the Arctic amplification of climate warming, the sea ice decline is associated with the snow/ice-albedo feedback effect (Flanner et al 2011;Graversen and Wang 2009;Serreze and Barry 2011), increased heat loss from the ocean (Screen and Simmonds 2010a, b), the water vapour and cloud radiative feedbacks (Sedlar et al 2011), and the small heat capacity of the shallow stably stratified boundary layer (Esau and Zilitinkevich 2010). It should be noted that there is no general consensus on the relative importance of various factors responsible for the Arctic amplification and sea ice decline.…”
Section: Reasons For the Sea Ice Declinementioning
confidence: 99%
“…Among the many processes that have been considered responsible for the Arctic amplification of climate warming, the sea ice decline is associated with the snow/ice-albedo feedback effect (Flanner et al 2011;Graversen and Wang 2009;Serreze and Barry 2011), increased heat loss from the ocean (Screen and Simmonds 2010a, b), the water vapour and cloud radiative feedbacks (Sedlar et al 2011), and the small heat capacity of the shallow stably stratified boundary layer (Esau and Zilitinkevich 2010). It should be noted that there is no general consensus on the relative importance of various factors responsible for the Arctic amplification and sea ice decline.…”
Section: Reasons For the Sea Ice Declinementioning
confidence: 99%
“…A certain heat input results in a larger temperature increase in a shallow than in a deep ABL. As the ABL is typically shallow in the Arctic, this may have contributed to the Arctic amplification of climate warming (Esau and Zilitinkevich, 2010;Esau et al, 2012). It is, however, not a positive feedback, as heating of the ABL tends to increase its thickness.…”
Section: Feedback Mechanismsmentioning
confidence: 99%
“…Flanner et al, 2011;Hudson, 2011); in addition to its direct effect, it enhances the Arctic amplification by strengthening the water vapour and cloud radiative feedbacks (Graversen and Wang, 2009). Further, feedbacks related to the shape of the temperature profile (Pithan and Mauritsen, 2014), the small heat capacity of the shallow stably stratified boundary layer (Esau and Zilitinkevich, 2010) and increased autumn-winter energy loss from the ocean (Overland et al, 2008;Screen and Simmonds, 2010a) tend to amplify Arctic warming as do the effects of aerosols. It has been suggested that black carbon aerosols reduce the surface albedo (e.g.…”
mentioning
confidence: 99%
“…It is now generally recognized that peculiarities of the stable ABL, including wave activity, affect not only regional weather, but also the general circulation of the atmosphere (see, e.g. Zilitinkevich and Esau 2003;Esau and Zilitinkevich 2010;Holtslag et al 2013;McGrath-Spangler et al 2015). A poor understanding of the exchange processes in the stable ABL and difficulties in its parametrization inhibit the development of numerical modelling of regional and local weather (Mahrt 1998;Cohen et al 2015).…”
Section: Introductionmentioning
confidence: 99%